2017
DOI: 10.1002/jcad.12134
|View full text |Cite
|
Sign up to set email alerts
|

Complicated Grief: An Evolving Theoretical Landscape

Abstract: The bereavement literature has proliferated in recent decades, generating a shift from conceptualizing grief as a stepwise, uniform process to an idiosyncratic experience that varies among individuals. Among the most notable developments is the empirical exploration of complicated grief—a protracted, debilitating, sometimes life‐threatening response to the death of a loved one—and the testing of novel interventions to treat it. This article provides counselors with recommendations for identifying and treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 68 publications
3
18
0
Order By: Relevance
“…Cancer caregivers are vulnerable to PGD, with Guldin et al (2011) reporting rates of 40% at 6 months, 28% at 13 months, and 27% at 18 months post bereavement. There has been considerable debate in the literature associated with PGD, CG and persistent complex bereavement disorder terminology (American Psychiatric Association, 2013;Crunk, Burke, & Robinson, 2017;Maciejewski, Maercker, Boelen, & Prigerson, 2016). This manuscript will use PGD to reflect all three terms.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer caregivers are vulnerable to PGD, with Guldin et al (2011) reporting rates of 40% at 6 months, 28% at 13 months, and 27% at 18 months post bereavement. There has been considerable debate in the literature associated with PGD, CG and persistent complex bereavement disorder terminology (American Psychiatric Association, 2013;Crunk, Burke, & Robinson, 2017;Maciejewski, Maercker, Boelen, & Prigerson, 2016). This manuscript will use PGD to reflect all three terms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the authors concluded that there is preliminary evidence for the helpfulness of CBT‐based interventions for bereaved persons, but studies on the relative efficacy of different cognitive‐behavioural change strategies, as well as other orientations, are still needed. As indicated in more recent review studies (Crunk, Burke, & Robinson, ; Shear, ), several randomized controlled trials have shown that a short‐term approach called complicated grief treatment is the treatment that has been most extensively studied so far (e.g., Boelen, de Keijser, van den Hout, & van den Bout, ; Bryant et al, ; Shear et al, ; Shear, Frank, Houck, & Reynolds, ). The treatment includes two main objectives: restoring effective functioning by generating enthusiasm and creating plans for the future and helping patients find a way to think about the death without having intense feelings of anger, guilt, or anxiety (Shear, ).…”
Section: Introductionmentioning
confidence: 99%
“…By normalizing her varied reactions and providing a safe space for Sophia to feel comfortable experiencing her emotions, a counselor would provide a conducive environment for emotional processing central to this second task. Additionally, because of some of Sophia's intensive symptoms, the counselor should screen for complicated or prolonged grief (Crunk et al, 2017) to determine how best to assist her in her grieving.…”
Section: Case Studymentioning
confidence: 99%